Le cadre déborde: framing Dora Maar's photographic works in dialogue with surrealism - Stewart, Naomi Isabella Jane (The University of Edinburgh, 2019)
The photographic oeuvre of the French artist Dora Maar (1907-1997) has remained critically neglected since her death over twenty years ago. Although several monographs addressing her life and art have been published in the intervening years, these texts centre on biography rather than analysis. This thesis therefore seeks to redress the peculiar want of recognition that Maar has faced. It mobilises critical-theoretical attention towards her photographic works, exploring their complex relations to their artistic contexts. Importantly, the thesis extends the analysis of Maar’s photography beyond the handful of overtly surreal, manipulated images that have, somewhat reductively, become representative of her association with surrealism. In doing so, it proposes a wider and more sustained dialogue between Maar’s work and surrealist principles than has been allowed for in the existing scholarship on the movement. Each chapter takes a specific image (or set of images) as its foundation and demonstrates how those images might be read through the lens of relevant theoretical frameworks and contextual details. The analysis opens with a chapter focusing on the nearest to a ‘canonical’ image that Maar has, Portrait d’Ubu (1936), employing surrealist and photography theory to consider how her ‘straight’ photographs can be seen to function as surreal. The second chapter addresses Maar’s street photography, exploring the mode and means of her movement throughout the urban environment, first through a situationist lens and, then, a more explicitly surrealist one. The third chapter provides a feminist critique of the gendered dynamics of the photographic encounter and the artistic-historical resonances of the images that result. The fourth and final chapters analyse, respectively, Maar’s engagement with the visual and the haptic, foregrounding sensory and psychoanalytic theory to evidence her resistance to hierarchical structures. Collectively, the thesis’ constituent chapters demonstrate the nuanced and varied dialogue between Maar’s photographic works and surrealism’s aesthetic and ideological principles.
Keywords: Dora Maar; photography; surrealism; Portrait d’Ubu; street photography